An Efficiency-Wage Model with Habit Concerns about Wages - Laszlo Goerke (Institute of Labor Economics (IZA), 2020)
We analyse the implications of habit formation relating to wages in a multi-period efficiency-wage model. If employees have such preferences, their existence provides firms with incentives to raise wages and reduce employment over time. Greater intensity does not necessarily have the same consequences, because wage adjustments counteract the initial level impact. The firm's response additionally depends on the wage-dependency of dismissal costs since such costs make an increasing wage profile more attractive and mitigate the effects of greater intensity of habit formation. We further show that short-lived productivity shocks have long-lasting wage and employment consequences. Moreover, habit concerns by firm owners reduce wages.
Keywords: D90; J31; J41; 330; efficiency wages; habit formation; wage profile; wage rigidity